(untitled) (AYUSHDHARA, 2021)
Poly Cystic Ovarian Disease (PCOD), Non-Alcoholic Fatty Liver Disease (NAFLD) and cholelithiasis are the major female health issues in the modern times having significant potential to increase the chances of infertility. The allopathic treatment of these conditions relies on suppressing the symptoms only and are also not afforded by all. But in Ayurveda a holistic approach to disease is followed. An effective management of all three conditions with Ayurveda is well described with the present case study. A 40 years old Hindu non-smoking, non-alcoholic female residing Noida presented to the OPD of Shuddhi Ayurveda Clinic, Jeena Sikho Lifecare Pvt. Ltd. Noida on 12 September, 2020. The patient was presented with her previous ultasonographic reports which indicated the worst condition of her liver along with polycystic ovary and gall bladder stone. After Ayurvedic treatment for the duration of almost 10 months, a remarkable change in the liver was observed with reduced values of liver parameters. The ultrasonic reports of after treatment showed negligible presence of ovarian cyst and bladder stone showing effectiveness of Ayurvedic treatment in the management of these diseases without any side effect.